Pemanfaatan metode forward chaining dalam mendiagnosa penyakit balita - Rebecca Irene Rolos; Vera Wijaya; Allwine; Lusianna Aritonang; Aliazer Hutapea (Jurnal Sains dan Teknologi Widyaloka (JSTekWid), 2022)
Children under the age of five (toddlers) are susceptible to disease. This is because the body's immune system is not strong enough to deal with viruses or germs from outside. Various types of diseases can attack the child's body so that parents need to be careful in seeing the child's health condition. research conducted by the Indonesian government or health problems that attack children under five still revolve around perinatal disorders, infectious diseases, and malnutrition. under-five mortality in Indonesia. Based on this case, in this study a system was created that can find out the toddler's disease based on the symptoms experienced and the disease will show the results of the symptom diagnosis. Identification of children's diseases in this study using the Forward Chaining method. This method is the right way to detect a disease, so users don't need to guess the disease suffered by the child because the system will provide answers based on existing facts. With the construction of this system, it is hoped that it will help parents to find out the symptoms of the disease suffered in toddlers and become an alternative for first aid.